Improving Problem-Solving Ability through a Constructivist Approach in Learning Mathematics for Grade X High School Students - Nasrianus Nampung; Aloisius Loka Son; Ferdinandus Mone (CV. Samuel Manurung and Co, 2023)
This study aims to improve students' problem-solving abilities through a constructivist approach. This study uses quantitative methods in the form of pre-experimental. This research was carried out in the even semester of the 2022/2023 academic year This research design used one group pretest and post-test. The participants of this study were 17 grade X students of one of the high schools in North Central Timor district. Research instruments in the form of problem-solving ability tests. Before conducting data analysis, a prerequisite test is first carried out, namely a normality test using the SPSS-assisted Shapiro-Wilk test, and the results obtained that the data is normally distributed. Test the hypothesis using a one-sample t-test and a paired sample t-test. The results showed that students who learned using the constructivist approach achieved minimal completeness and there was an increase in the mathematical problem-solving ability of students who learned through the constructivism approach. Learning with a constructivist approach can facilitate the problem-solving ability of high school students. Therefore, it is recommended that advanced researchers in order to be able to apply constructivist approaches to other mathematical abilities